Role of Place in Explaining Racial Heterogeneity in Cognitive Outcomes among Older Adults. (28th September 2015) - Liu, Sze Yan; Glymour, M. Maria; Zahodne, Laura B.; Weiss, Christopher; Manly, Jennifer J.
Abstract: Racially patterned disadvantage in Southern states, especially during the formative years of primary school, may contribute to enduring disparities in adult cognitive outcomes. Drawing on a lifecourse perspective, we examine whether state of school attendance affects cognitive outcomes in older adults and partially contributes to persistent racial disparities. Using data from older African American and white participants in the national Health and Retirement Study (HRS) and the New York based Washington Heights Inwood Cognitive Aging Project (WHICAP), we estimated age-and gender-adjusted multilevel models with random effects for states predicting years of education and cognitive outcomes (e.g., memory and vocabulary). We summarized the proportion of variation in outcomes attributable to state of school attendance and compared the magnitude of racial disparities across states. Among WHICAP African Americans, state of school attendance accounted for 9% of the variance in years of schooling, 6% of memory, and 12% of language. Among HRS African Americans, state of school attendance accounted for 13% of the variance in years of schooling and also contributed to variance in cognitive function (7%), memory (2%), and vocabulary (12%). Random slope models indicated state-level African American and white disparities in every Census region, with the largest racial differences in the South. State of school attendance may contribute to racial disparities in cognitive outcomes among older Americans. Despite tremendous within-state heterogeneity, state of school attendance also accounted for some variability in cognitive outcomes. Racial disparities in older Americans may reflect historical patterns of segregation and differential access to resources such as education. ( JINS, 2015, 21, 677–687)